Urinary excretion profiles of 11-nor-9-carboxy-Delta9-tetrahydrocannabinol: a Delta9-THC-COOH to creatinine ratio study #2 - Fraser, Albert D; Worth, David (Forensic science international, 2003)
Subjects with a history of chronic marijuana use were screened for cannabinoids in urine specimens with the EMIT((R)) II Plus cannabinoids assay with a cut-off value of 50 ng/ml. All presumptively positive specimens were submitted for confirmatory analysis for the major urinary cannabinoid metabolite (Delta(9)-THC-COOH) by GC-MS with a cut-off value of 15 ng/ml. Creatinine was analyzed in each specimen as an index of dilution. Huestis and Cone [J. Anal. Toxicol. 22 (1998) 445] reported that serial monitoring of Delta(9)-THC-COOH to creatinine ratios in paired urine specimens collected at least 24h apart could differentiate new drug use from residual Delta(9)-THC-COOH excretion. The best accuracy (85.4%) for predicting new marijuana use was a Delta(9)-THC-COOH/creatinine ratio > or =0.5 (dividing the Delta(9)-THC-COOH to creatinine ratio of specimen 2 by the specimen 1 ratio). In a previous study in this laboratory [J. Anal. Toxicol. 23 (1999) 531], urine specimens were collected from chronic marijuana users at least 24h apart and dilute urine specimens (creatinine values <2.2 micromol/l) were excluded from the data analysis. The objective of the present study was to determine whether creatinine corrected urine specimens positive for cannabinoids could differentiate new marijuana use from the excretion of residual Delta(9)-THC-COOH in chronic users of marijuana based on the Huestis 0.5 ratio. Urine specimens (N=946) were collected from 37 individuals with at least 48h between collections. All urine specimens were included in the data review irrespective of creatinine concentration. The mean urinary Delta(9)-THC-COOH concentration was 302.4 ng/ml, mean Delta(9)-THC-COOH/creatinine ratio (ng/ml Delta(9)-THC-COOH/(mmol/l) creatinine) was 29.3 and the Huestis ratio calculation indicated new drug use in 83% of all sequentially paired urine specimens. The data were sub-divided into three groups (A-C) based on the mean Delta(9)-THC-COOH/creatinine values. Interindividual Delta(9)-THC-COOH/creatinine mean values ranged from 2.2 to 13.8 in group A (264 specimens, N=15 subjects) where 80.7% of paired specimens indicated new drug use. In group B, mean Delta(9)-THC-COOH/creatinine values ranged from 15.3 to 37.8 in 444 specimens (N=14 subjects) and 83.3% of paired specimens indicated new drug use. In group C, individual mean Delta(9)-THC-COOH/creatinine values were >40.1 (41.3-132.5) in 238 urine specimens (N=8 subjects) and 85.3% of paired urine specimens indicated new marijuana use. Correcting Delta(9)-THC-COOH excretion for urinary dilution and comparing Delta(9)-THC-COOH/creatinine concentration ratios of sequentially paired specimens (collected at least 48h apart) provided an objective indicator of new marijuana use in this population.